Internet-delivered Cognitive Behavioral Therapy for Premenstrual Dysphoric Disorder targeting emotion dysregulation: Study protocol for a randomised controlled trial - Hoppe, Johanna Motilla; Kleinstaeuber, Maria; Andersson, Gerhard; Skalkidou, Alkistis; Vegelius, Johan; Comasco, Erika; Kaltsouni, Elisavet; Buhrman, Monica; Weise, Cornelia (7. European Society for Cognitive and Affective Neuroscience (ESCAN) meeting, 2024)
Introduction. Premenstrual dysphoric disorder (PMDD) is a highly debilitating cyclic condition affecting about 5% of women of reproductive age. PMDD is characterised by intense premenstrual symptoms such as mood swings, irritability, and depressed mood, often leading to emotion dysregulation. Although pharmacological interventions are available, many women experience residual symptoms, discontinue treatment, or refrain from them due to side effects. Therefore, readily accessible non-pharmacological interventions are needed as an alternative or complement. Preliminary findings suggest that Internet-delivered cognitive behavioural therapy (iCBT) may be a promising avenue. However, further research is warranted to establish its effects and dismantle its active components. This upcoming study will evaluate an iCBT protocol for PMDD targeting emotion dysregulation in a randomised controlled study and examine the link between emotion regulation difficulties and treatment response. Methods. One hundred sixty women (age 18-45) fulfilling the diagnostic criteria for PMDD will be randomly assigned to eight weeks of guided self-help iCBT or waiting list. The treatment includes psychoeducation, emotion regulation strategies, cognitive techniques, and health-promoting behaviours. Treatment effects on PMDD symptoms, psychological and functional impairment, quality of life and emotion regulation difficulties will be evaluated using linear mixed models. Long-term treatment effects will be assessed 6 and 12 months post-treatment. The link between emotion regulation capacity and symptom reduction will be examined using Gaussian process modelling. Recruitment is planned for August 2024. Main conclusions. The study will elucidate the potential utility of iCBT as an alternative to pharmacological interventions and the relationship between emotion dysregulation and treatment respons